Search for the charged-lepton-flavor-violating decay Z ? e? in pp collisions at ?s=13 TeV with the ATLAS detector - Çetin, Serkant Ali (AMER PHYSICAL SOC, 2023)
A search for the charged-lepton-flavor-violating process Z -> e mu is presented, using 139 fb(-1) of root s = 13 TeV pp collision data collected by the ATLAS experiment at the LHC. An excess in the e mu invariant mass spectrum near the Z boson mass would be a striking signature of new physics. No excess is observed, and an upper limit B(Z -> e mu) < 2.62 x 10(-7) is placed on the branching fraction at 95% confidence level, which is the most stringent limit to date.